Acid dissolution of neodymium magnet Nd-Fe-B in different conditions - Ismailova, A.G.; Akanova, G.Zh.; Kamysbayev, D.Kh. (KU Publ., 2021)
The separation of rare-earth elements (REE) from a neodymium magnet has been widely studied last year. During the research it was identified that the waste of computer hard disk contains 25.41 % neodymium, 64.09 % iron, and <<1 % boron. To further isolate rare-earth metals, the magnet was acidically dissolved in open and closed systems. In both methods of dissolution, concentrated nitric acid was used. The difference between these methods is the conditions of dissolution of magnet. The magnet was dissolved in a microwave sample preparation system at different temperatures and pressures in a closed system. In the open system, the acid dissolution of the magnet is conducted at room temperature. 0.2 g of the neodymium magnet sample was taken under two conditions, and the dissolution process in the closed system lasted 1 hour, and in the open system 30-40 minutes. The open system is a non-laborious, simple, and cheap method of dissolving the magnet by comparing both systems. Therefore, an open sample preparation system is used for further work. To remove the iron in the magnet, oxalic acid was used and REEs are precipitated as oxalates under both conditions. According to the result of the Inductively coupled plasma mass spectrometry (ICP-MS) method, it was identified that the neodymium and iron contents in the precipitate are 24.66 % and 0.06 %, respectively. This shows that the iron has almost completely passed to the filtrate.
Әртүрлі жағдайда Nd-Fe-B неодимді магнитті қышқылдық еріту
Кислотное растворение неодимового магнита Nd-Fe-B в различных условиях
Keywords: acid dissolution; neodymium magnet; rare-earth metals; neodymium; praseodymium; dysprosium; open system; microwave sample preparation system; ICP-MS analysis